Extraction of “Quercetin-Rich” Red Onion Skin with Acetone and Chemical Modification using Aromatic Diazonium Salts - Manizabayo, Gervais; Chukwu, Uche John; Abayeh, Ovi Julius (Makara Journal of Science, 2019)
The extraction of “quercetin-rich” red onion skin (red onion skin extract [ROSE]) using acetone and chemical modification with aromatic diazonium salts of aniline (AmROSE), 2-aminophenol (APmROSE), and 2-aminobenzoic acid (ABmROSE) were carried out in this study. The effects of the particle diameter of red onion skin (ROS), volume of the solvent, and percentage of acetone in the solvent mixture on the extraction yield were investigated. The solubility, color, melting point, and functional groups present in ROSE before and after modification were also analyzed. The extraction of ROS using an aqueous solvent of 50% acetone gave the highest percentage extraction yield. In addition to the C=O, OH, C-O-C, and C-O-H functional groups that were present in both unmodified ROSE (UROSE) and modified ROSE, Infrared spectra results revealed that all the modifications (AmROSE, APmROSE, and ABmROSE) showed the presence of N=N and C-N of aromaticazo compounds at 1512–1496 and 1288–1256 cm−1, respectively. The three modifications were also found to be more soluble than UROSE in all the solvents. The melting point of UROSE and its modifications was within the range of 78 °C–105 °C, which was lowerthan that of commercial quercetin dehydrate P-Q (300 °C–310 °C).